2018
DOI: 10.1371/journal.pntd.0006450
|View full text |Cite
|
Sign up to set email alerts
|

Benzoxaborole treatment perturbs S-adenosyl-L-methionine metabolism in Trypanosoma brucei

Abstract: The parasitic protozoan Trypanosoma brucei causes Human African Trypanosomiasis and Nagana in other mammals. These diseases present a major socio-economic burden to large areas of sub-Saharan Africa. Current therapies involve complex and toxic regimens, which can lead to fatal side-effects. In addition, there is emerging evidence for drug resistance. AN5568 (SCYX-7158) is a novel benzoxaborole class compound that has been selected as a lead compound for the treatment of HAT, and has demonstrated effective clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 67 publications
2
39
0
1
Order By: Relevance
“…Polyadenylation and trans-splicing of adjacent genes are coupled in trypanosomatids, however (42), and consistent with this, CPSF3 knockdown disrupted both polyadenylation and trans-splicing in T. b. brucei (49). Accordingly, inhibition of CPSF3 may explain perturbed methyl-donor metabolism after acoziborole exposure (25), which may be because of reduced mRNA methylation as a result of a splicing defect. CPSF3 also associates with the U1A snRNP splicing complex in trypanosomatids (50).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Polyadenylation and trans-splicing of adjacent genes are coupled in trypanosomatids, however (42), and consistent with this, CPSF3 knockdown disrupted both polyadenylation and trans-splicing in T. b. brucei (49). Accordingly, inhibition of CPSF3 may explain perturbed methyl-donor metabolism after acoziborole exposure (25), which may be because of reduced mRNA methylation as a result of a splicing defect. CPSF3 also associates with the U1A snRNP splicing complex in trypanosomatids (50).…”
Section: Discussionsupporting
confidence: 61%
“…Oxaboroles are also potential antihypertensive rho-activated kinase inhibitors (22) and anti-inflammatory phosphodiesterase inhibitors for the treatment of psoriasis (23). Genomic and proteomic approaches, using oxaborole-1, a close analog of acoziborole, previously yielded lists of candidate genes implicated in the antitrypanosomal mode of action (24), whereas metabolomic analysis after acoziborole exposure indicated perturbation of S-adenosyl-L-methionine metabolism (25), but the trypanocidal targets of acoziborole and AN11736 remained unknown.…”
Section: Significancementioning
confidence: 99%
“…This results in loss of mRNA from the cells by the normal mechanisms of mRNA turnover [ 49 ]. It has recently been shown that an accumulation of numerous metabolites, including S-adenosylmethionine, occurs in trypanosomes treated with Sinefungin, and a similar profile was identified in trypanosomes treated with acoziborole [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, CPSF3 was identified as a target for benzoxaboroles in apicomplexan parasites Plasmodium [93] and Toxoplasma [94]. Based on this observation, and the fact that metabolomics experiments had revealed a profound change in the methionine metabolism [95] that might have been related to RNA processing defects, particularly given the multi-methylation of the spliced leader sequence used in trans-splicing in trypanosomes, the effect of over-expression of CPSF3 on sensitivity to the related benzoxaborole, AN7973, was tested [96].…”
Section: Acoziborole: Mode Of Action and Resistance Riskmentioning
confidence: 99%